The Impact of Poverty on Human Health and Well-being: A Qualitative Exploratory Study - Khumalo, Mandla; Dunn, Nonhlanhla (Journal of Current Social and Political Issues, 2025)
Poverty remains a global challenge affecting multiple dimensions of human life. Health and well-being play a pivotal role in sustaining economies, politics and life. This study examines the impact of poverty on the health and well-being of humanity and assesses its effects on the economy. It identifies the underlying drivers of poverty and how to address them. A qualitative exploratory framework from a theological perspective was employed. Data were collected from 32 participants aged 18 – 67 through semi-structured interviews, and participants were purposively selected. Using thematic data analysis approach three main themes emerged. The findings indicate a strong correlation between poverty, economic growth, well-being and human health. Poverty affects livelihoods and has significant social and emotional effects including loneliness, discrimination, hypertension, cardio-vascular disorders and substance abuse. Furthermore, poverty has a bidirectional relationship with economic development and migration, reflecting both positive and negative influences. The study underscores the need to strengthen social protection policies and consider shifting paradigms of poverty that support and constrain contemporary policy. Further research is necessary to ascertain the drivers of poverty and improve eradication strategies. Multi-sectorial collaboration involving the state, NGOs, and religious organizations is recommended.